Holiday collector's set. Vol. 3 - Quinn, Aidan; Bassett, Angela; Zuniga, Daphne, 1962-; Echo Bridge Home Entertainment ([United States] : Echo Bridge Home Entertainment, 2011)
6 movie collector's set includes: A Family Thanksgiving, I'll Be Home For Christmas, Borrowed Hearts, Music of the Heart, A Christmas Without Snow, and A Child's Christmas in Wales, plus bonus audio: Home For the Holidays.
A Family Thanksgiving -- I'll Be Home For Christmas -- Borrowed Hearts, Music of the Heart -- A Christmas Without Snow -- A Child's Christmas in Wales.
Title from sell sheet.
Aidan Quinn, Angela Bassett, Daphne Zuniga, Denholm Elliott, Eric McCormack, Faye Dunaway, Jack Palance, Michael Angarano, Michael Learned, Gloria Estefan, Hector Elizondo, Meryl Streep, Roma Downey.
DVD, region 1, NTSC.
Keywords: Feature films; Christmas films